Glucose Transporter Mutants of Escherichia coli K-12 with Changes in Substrate Recognition of IICB(Glc) and Induction Behavior of the ptsG Gene - Zeppenfeld, Tim (American Society for Microbiology, 2000)
In Escherichia coli K-12, the major glucose transporter with a central role in carbon catabolite repression and in inducer exclusion is the phosphoenolpyruvate-dependent glucose:phosphotransferase system (PTS). Its membrane-bound subunit, IICB(Glc), is encoded by the gene ptsG; its soluble domain, IIA(Glc), is encoded by crr, which is a member of the pts operon. The system is inducible by d-glucose and, to a lesser degree, by l-sorbose. The regulation of ptsG transcription was analyzed by testing the induction of IICB(Glc) transporter activity and of a single-copy Φ(ptsGop-lacZ) fusion. Among mutations found to affect directly ptsG expression were those altering the activity of adenylate cyclase (cyaA), the repressor DgsA (dgsA; also called Mlc), the general PTS proteins enzyme I (ptsI) and histidine carrier protein HPr (ptsH), and the IIA(Glc) and IIB(Glc) domains, as well as several authentic and newly isolated UmgC mutations. The latter, originally thought to map in the repressor gene umgC outside the ptsG locus, were found to represent ptsG alleles. These affected invariably the substrate specificity of the IICB(Glc) domain, thus allowing efficient transport and phosphorylation of substrates normally transported very poorly or not at all by this PTS. Simultaneously, all of these substrates became inducers for ptsG. From the analysis of the mutants, from cis-trans dominance tests, and from the identification of the amino acid residues mutated in the UmgC mutants, a new regulatory mechanism involved in ptsG induction is postulated. According to this model, the phosphorylation state of IIB(Glc) modulates IIC(Glc) which, directly or indirectly, controls the repressor DgsA and hence ptsG expression. By the same mechanism, glucose uptake and phosphorylation also control the expression of the pts operon and probably of all operons controlled by the repressor DgsA.